WOMEN INFORMAL WORKERS' RESILIENCE DURING THE HEALTH EMERGENCY: A CASE STUDY IN KETITANG VILLAGE, BOYOLALI - Hayati, Beti Nur (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
The health emergency situation has brought about various negative impacts, one of which is the economic shock experienced by female workers during the pandemic. According to the National Labor Force Survey (Sakernas) conducted in February 2020, 61.35% of female workers were employed in the informal sector. Women working in the informal sector often face greater challenges, such as the lack of social protection, income insecurity, and limited access to financial and social support. This means that 6 out of 10 working women were significantly affected due to their employment in the informal sector. Efficiency measures in informal enterprises had a direct impact on female workers, resulting in many of them being severely affected by the economic crisis caused by the pandemic. Moreover, many of these women carry double responsibilities, both in domestic roles and as breadwinners, which exacerbates their vulnerability amid ongoing economic uncertainty. This study employs a qualitative method through in-depth interviews and focus group discussions (FGDs) conducted in Ketitang Village, Boyolali Regency. The village hosts four medium and large-scale companies employing 1,150 workers, 25 small industries with 168 workers, 25 home industries with 50 workers, and 37 food stalls employing 71 workers. The objective of this study is to explore the resilience strategies adopted by informal female workers in Ketitang, Nogosari. The resilience strategies of informal female workers are analyzed using Grottberg’s conceptual framework of “I am, I can, I have.” The findings of this study reveal that strong family and community support, access to social security, and a belief in economic recovery are the main sources of their resilience. Cooperation with partners and empathy among fellow workers also play a crucial role in strengthening their economic resilience.